Linking soil organic carbon mineralization to soil physicochemical properties and bacterial alpha diversity at different depths following land use changes - Guo, Jing; Xiong, Wulai; Qiu, Jian; Wang, Guibin (Ecological processes, 2023)
Background Anthropogenic land use changes (LUCs) impart intensifying impacts on soil organic carbon (SOC) turnover, leading to uncertainty concerning SOC mineralization patterns and determining whether soils act as “source” or “sink” in the global carbon budget. Therefore, understanding the SOC mineralization characteristics of different LUC patterns and their potential influencing factors is crucial. An indoor incubation experiment was conducted to study the SOC mineralization patterns and their relevance to soil physicochemical properties, soil enzyme activity, SOC fractions, and bacterial alpha diversity. The soils were collected from two layers of five typical LUC patterns in Yellow Sea Forest Park, including four that were converted from wheat–corn rotation systems [a gingko plantation (G), a metasequoia plantation (M), a gingko–wheat–corn agroforestry system (GW), and a gingko–metasequoia system (GM)] and a traditional wheat–corn system (W). Results LUCs had significant and diverse impacts on the SOC content and SOC fraction contents and on soil enzyme activity. The cumulative SOC mineralization was significantly higher in the M systen than in the W and GW systems at 0–20 cm depth and higher in the G system than in the GW system at 20–40 cm depth after 60-day incubation. The mineralization ratio was highest in the W system and lowest in the GW system. The soil pH and bulk density had a significant negative correlation with the cumulative SOC mineralization, while the soil bacterial Shannon index had a significant positive correlation with cumulative SOC mineralization. Multiple stepwise linear regression analysis showed that the SOC mineralization potential was dominantly explained by the bacterial Shannon index and operational taxonomic units (OTUs). The GW system had lower potentially mineralizable SOC and higher SOC stability. Additionally, the incubation time and cumulative SOC mineralization were well fitted by the first-order kinetic equation. Conclusions LUCs significantly changed SOC mineralization characteristics and the results highlighted the important roles of the bacterial community in soil carbon cycling, which contributes to the fundamental understanding of SOC turnover regulation.